The Impact of The 2020 Health Crisis on Exchange Rates and Stock Prices in Indonesia : (Study on PT. Jasa Marga (Persero) Tbk.) - Rofik Efendi; Yuliani; Sri Anugrah Natalina (Department of Islamic Accounting, The Faculty of Islamic Economics and Business, State Islamic Institute of Kediri [IAIN Kediri, 2023)
The infrastructure sector during the health crisis had an impact by declining by around 12% until the end of 2020. One that can cause a decrease in stock prices is the exchange rate. PT Jasa Marga (Persero) Tbk. is one of the companies that showed active stock price activity during the health crisis period. The data sample of this study is to take daily data from exchange rates and stock prices during 2020 with a sample number of 242. Empirical results show that the correlation coefficient is -0.89, hence the relationship between the exchange rate and stock price is very strong and contradictory. Ha's partial test results were accepted and Ho was rejected, i.e. the exchange rate was partially significant and affected the stock price. The R square results of 79.8 percent that the exchange rate .